A New Route to E‐Stilbenes through the Transition‐Metal‐Free KOtBu/DMF‐Promoted Direct Coupling of Alcohols with Phenyl Acetonitriles. Issue 26 (9th July 2022) - Liu, Xiaoping; Sotiropoulos, Jean‐Marc; Taillefer, Marc
Abstract: An alternative route to synthesise alkenes, based only on the KO t Bu/DMF promoted activation and direct coupling of alcohols with phenyl acetonitriles, is reported. Various E ‐stilbenes have thus been obtained directly from alcohols that are sustainable sources of carbon, which to our knowledge, is unprecedented in the absence of transition metal based catalysts. A variation allowing, through a Csp3 −Csp3 bond formation, the selective synthesis of N ‐Heteroarenes is also described. A mechanism for the olefination pathway proceeding via an original activation of alcohols under alkyl formates is provided. Abstract : A new route to E ‐Stilbenes, based on the transition metal free, KO t Bu/DMF promoted activation and direct coupling of alcohols with phenyl acetonitriles, is reported. A variation allowing the selective synthesis of N‐Heteroarenes and a mechanism proceeding via the activation of alcohols under alkyl formate intermediates are also reported.